Effects of front-of-package caffeine and sweetener disclaimers in Mexico: cross-sectional results from the 2020 International Food Policy Study - Laura Patricia Arellano-Gómez; Alejandra Jáuregui; Claudia Nieto; Alejandra Contreras-Manzano; Kathia Larissa Quevedo; Christine M White; James F Thrasher; Rachel E Davis; David Hammond; Simón Barquera (Public Health Nutrition, 2023)
Abstract